Citric Acid Conditioning as an Alternative to EDTA for Growth Factors Release and Stem Cell Response in Regenerative Endodontics: A Systematic Review of In Vitro Studies - Reis-Prado, A.H. dos; Toledo, P. T.A. [UNESP]; Nunes, G. P.; Ferreira, P. A.V.; Rahimnejad, M.; Dal-Fabbro, R.; Abreu, L. G.; Bottino, M. C.; Benetti, F. (Elsevier, 2024)
Introduction: Citric acid (CA) conditioning may be a promising alternative to ethylenediaminetetraacetic acid (EDTA) in regenerative endodontic procedures, as reported to improve growth factors’ release from dentin. This review systematically investigated the effect of CA conditioning on the growth factors release from dentin and cell behavior compared to EDTA conditioning. Methods: Searches were conducted (PubMed/MEDLINE, Scopus, Web of Science, Embase, SciELO, Cochrane Library, and grey literature) until May-2023. Only in vitro studies that evaluated the effects of CA on growth factors' release from dentin and cell behavior outcomes compared to EDTA were included. The studies were critically appraised using a modified Joanna Briggs Institute's checklist. Meta-analysis was unfeasible. Results: Out of the 335 articles screened, nine were included. Among these, three studies used dentin discs/roots from permanent human teeth; the rest combined them with stem cells. 10% CA for 5 or 10 minute was the most used protocol. Meanwhile, EDTA concentrations ranged from 10% to 17%. In eight studies examining the release of growth factors, five reported a significant release of transforming growth factor-β after dentin conditioning with 10% CA compared to 17% EDTA. Regarding cell behavior (6 studies), three studies assessed cell viability. The findings revealed that 10% CA conditioning showed cell viability similar to those of 17% EDTA. Additionally, in two out of three studies, it was observed that 10% CA conditioning did not affect cell morphology. The studies had a low risk of bias. Conclusions: The use of 10% CA to condition dentin for 5-10 minutes resulted in a notable transforming growth factor -β1 release, but its cell responses were similar to those of EDTA.
Keywords: Citric acid; EDTA; growth factor(s); regenerative endodontics; stem cells; systematic review